VICENNIAL GROWTH OF ECOPRENEURSHIP AS A RESEARCH FIELD - Guleria, Deepa; Kaur, Gurvinder; Kaur, Gurvinder; Kaur, Sukhpreet; Singh, Deler (International Journal of Psychosocial Rehabilitation, 2020)
Interestingly, since last two decades ecopreneurship has received recognition from academicians and researchers, with few conceptual and empirical contributions and increasing publications. Ecopreneurship is an emerging field as a convergent of ecology and entrepreneurship that should be embedded within the economic activities to transcend its impact in environment conversation and commitment. Through using bibliometric database and techniques, this study analyses the academic literature on ecopreneurship and give a brief representation of the contributions in the field and highlights further need for its expansion as a research field. The literature analysis from the Web of Knowledge (Thomson Reuters) database—until December 2019— provides some surprising insights pertaining to various articles, journals who been the catalysts in the emergence of this field and highlighting its importance. As a result, out of a total 30 articles from Web of Science (WOS) since its inception (1998) to 2019 were retrieved. After applying various inclusion criterions on these we could finally identify the most significant articles. The analysis identifies acceptance for these neophyte publications and opportunities for further research.